The Role of SPINK1 in ETS Rearrangement Negative Prostate Cancers - Tomlins, Scott A. (2008)
ETS gene fusions have been characterized in a majority of prostate cancers, however the key molecular alterations in ETS negative cancers are unclear. Here we used an outlier meta-analysis (meta-COPA) to identify SPINK1 outlier-expression exclusively in a subset of ETS rearrangement negative cancers (~10% of total cases). We validated the mutual exclusivity of SPINK1 expression and ETS fusion status, demonstrated that SPINK1 outlier-expression can be detected non-invasively in urine and observed that SPINK1 outlier-expression is an independent predictor of biochemical recurrence after resection. We identified the aggressive 22RV1 cell line as a SPINK1 outlier-expression model, and demonstrate that SPINK1 knockdown in 22RV1 attenuates invasion, suggesting a functional role in ETS rearrangement negative prostate cancers.